Bridging Sustainability and Pedagogy: A Narrative Review of Education for Sustainable Development (ESD) Implementation in Indonesian Science Education - Nugroho, Unggung Eri; Nugroho, Ary Susatyo; Hayat, Muhammad Syaipul; Patonah, Siti (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2025)
This narrative review explores the integration of Education for Sustainable Development (ESD) within Indonesian science education, focusing on elementary to upper secondary levels between 2020 and 2024. The study aims to analyze how ESD has been operationalized across science subjects—particularly in physics, biology, and interdisciplinary IPAS—through various instructional models. It further evaluates curriculum alignment, identifies implementation challenges, and highlights pedagogical innovations that support sustainable learning outcomes. Using a narrative synthesis approach, ten empirical studies were examined based on inclusion criteria emphasizing Indonesian science contexts, ESD orientation, and modular or project-based designs. Data were organized into six thematic categories: STEAM integration, differentiated instruction, project-based learning, ecoliteracy, digital media, and curriculum-policy gaps. Tabled analyses captured subject focus, instructional tools, ESD competencies addressed, and reported outcomes. The review finds that while teachers frequently initiate ESD-based practices through creative instructional strategies—such as ProBLES, PJBL, and ecoliteracy modules—systemic curriculum integration remains limited. Notably, the absence of formal ESD indicators in core topics like rotational dynamics constrains scalability. Nonetheless, significant cognitive and affective gains were observed, including increases in critical thinking, creativity, environmental care, and systems awareness. Community partnerships and digital media tools also show potential to amplify ESD awareness among young learners. These findings suggest a pressing need for structured curriculum reform and professional development to institutionalize ESD in science education. The review contributes a nuanced understanding of localized ESD practice and offers a roadmap for aligning policy, pedagogy, and sustainability competencies.